2015
DOI: 10.1111/ppa.12335
|View full text |Cite
|
Sign up to set email alerts
|

The endophytic fungus Piriformospora indica protects wheat from fusarium crown rot disease in simulated UK autumn conditions

Abstract: The root endophytic fungus Piriformospora indica (Sebacinacea) forms mutualistic symbioses with a broad range of host plants, increasing their biomass production and resistance to fungal pathogens. This study evaluated the effect of P. indica on fusarium crown rot disease of wheat, under in vitro and glasshouse conditions. Interaction of P. indica and Fusarium isolates under axenic culture conditions indicated no direct antagonistic activity of P. indica against Fusarium isolates. Seedlings of wheat were inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 31 publications
5
23
0
Order By: Relevance
“…This is in agreement with the results of histological studies performed with the fungus on other plants colonized by P. indica such as wheat (Serfling et al, 2007;Yilmaz, 2013;Rabiey et al, 2015;Moharam et al, 2017), barley (Waller et al, 2007;Yilmaz, 2013), maize (Kumar et al, 2009;Rane et al, 2015) and rice (Bagheri et al, 2014). Colonization of cucumber roots with P. indica was also confirmed by PCR diagnosis.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This is in agreement with the results of histological studies performed with the fungus on other plants colonized by P. indica such as wheat (Serfling et al, 2007;Yilmaz, 2013;Rabiey et al, 2015;Moharam et al, 2017), barley (Waller et al, 2007;Yilmaz, 2013), maize (Kumar et al, 2009;Rane et al, 2015) and rice (Bagheri et al, 2014). Colonization of cucumber roots with P. indica was also confirmed by PCR diagnosis.…”
Section: Discussionsupporting
confidence: 80%
“…In these test, a clear antagonism between both fungi was not found. A lack of an antagonistic effect of P. indica on other species of Fusarium such as F. culmorum, F. graminearum, F. verticillioides or F. oxysporum causing root diseases on different plants has been reported before (Deshmukh and Kogel, 2007;Kumar et al, 2009;Rabiey et al, 2015;Moharam et al, 2017). Also, on agar media amended with culture filtrate of P. indica a negative effect on mycelial growth of Fo was not seen (data not shown), confirming the results of the dual culture test.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Inoculum was prepared according to the methods described by Rabiey et al . (). Piriformospora indica liquid culture containing an unquantified mixture of chlamydospores and mycelium was used for inoculation by mixing with soil at sowing time.…”
Section: Methodsmentioning
confidence: 97%
“…hordei) under glasshouse and field conditions (Ghahfarokhy et al, 2011;Waller et al, 2005;Deshmukh & Kogel, 2007;Harrach et al, 2013). Previous work has shown that P. indica association protects wheat seedlings from FCR damage in simulated UK autumn conditions (Rabiey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%